The Role of Television in Creating Anxiety by the University's Readers (Raparin Journal of Humanities (RJH), 2021)
The purpose of this research is:-• Knowing the role of television in creating anxiety among students in general.• Knowing the role of television in creating anxiety among students according to gender change.• Knowing the role of television in creating anxiety among students according to the changing stages       Researchers have prepared a scale for conducting their research, the most important of which is the statistics used, including SPSS person and t-tests. The most important results of the study have shown that television plays a role in creating anxiety by the study participants. There are no differences according to gender and different stages. Thus, at the result, this research eventually came up with some suggestions: monitoring TV shows and limiting the presentation of programs that cause fear and anxiety to the audience.• Providing the psychological and social researchers on the television staff to evaluate and bowdlerize any programs before broadcasting.• Knowing the television efforts to postpone programs that cause fear and anxiety when they are promoted.• Monitoring the dramas performed on some channels, because some of them are incompatible with culture and social values, will cause fear and anxiety for the audience.